The Influence of Financial Planning, Budget Control, And Risk Management on Project Performance Through the Mediation of Technological Innovation - MT, Ir. Eko Budi Satoto, M.; Akun, Budi Santoso, SE., MM, M. (Journal of Posthumanism, 2026)
This research is motivated by the importance of improving the performance of infrastructure construction projects in the midst of limited resources and efficiency demands in developing countries such as Indonesia. Managerial practices such as financial planning, budget control, and risk management are often considered to be key factors, but have not been able to fully explain variations in project performance without considering the role of technological innovation. This study aims to analyze the influence of financial planning, budget control, and risk management on project performance with technological innovation as an intervening variable. The research method used is a quantitative approach by collecting data through surveys of respondents involved in infrastructure construction projects, then analyzed using a structural modeling approach. The results of the study show that budget control has a significant effect on project performance both directly and indirectly, while financial planning and risk management do not have a direct effect, but have a significant effect through technological innovation. In addition, technological innovation has proven to have an important role in improving project performance as the main mediator. The implications of this study confirm that organizations need to integrate managerial practices with the development of technological innovations to improve the effectiveness and sustainability of project performance.